Systems for Drug Delivery Safety, Animal, and Microbial Polysaccharides - Bhatia, Saurabh; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book details current developments in all natural polymers, with a focus on animal and microbial polysaccharides. The book examines, compares, and contrasts the efficiency of plant and algae based natural polymers in inducing immune reactions. Additionally, the book details the safety and toxicity profiles with respective regulations.
Ch.1. Mammalian Polysaccharides and Its Nanomaterials -- Ch.2. Microbial Polysaccharides as Advance Nanomaterials -- Ch.3. Chitosan Based Nanomaterials and Its Applications -- Ch.4. Advance Polymers and Its Applications -- Ch.5. Advanced Application of Natural Polysaccharides -- Ch.6. Modern Polysaccharides and Its Current Advancements -- Ch.7. Toxicity of Nanodrug Delivery Systems.
Keywords: Polymers; Polymers